Operation:Orfeo - its Act of Enunciation - Kyndrup, Morten (Peripeti, 2017)
Operation:Orfeo is a theatrical spectacle of a very particular nature, lasting some 80 minutes. It unfolds in a separate scenic space mounted on the stage. This scenic space is comprised of a thick picture frame surrounding a square space, measuring 6x6 meters, inside which a staircase is mounted, across the entire width of the square, from top to bottom. The stairs are lit in such a way that the space does not unfold unambiguously both horizontally and vertically (as staircases usually do). It primarily appears vertical, as a surface provided with a horizontal grid, fastened in a picture frame. In this room, on these stairs, a total of 14 players sing in different positions all through the performance.